Diversity of filter feeding and variations in cross-flow filtration of five ram-feeding fish species - Hamann, Leandra; Schreiber, Kristina; Hagenmeyer, Jan; Eduardo, Santiago; Spanke, Tobias; Blanke, Alexander (Frontiers in Marine Science, 2023)
Introduction Filter-feeding fish separate food particles from the surrounding water by cross-flow filtration in which a suspension flows parallel to a porous filter medium, thereby transporting particles along the surface. Methods Here, we investigate cross-flow filtration in five ram-feeding fish species from two groups, Scombridae (Scomber scombrus and Rastrelliger kanagurta) and Clupeidae (Clupea harengus, Sardina pilchardus, and Engraulis encrasicolus). Using a combination of morphometrics, micro-CT scanning, video analysis, and water tunnel experiments, we give a detailed description of the gill arch system, calculate filtration parameters, observe particle movement, and identify morphological traits that induce cross-flow filtration. Results Our findings suggest that these ram-feeding fish species use a combination of cross-flow and dead-end filtration as the underlying filtration principle. Specifically, the particles are transported along the surface of gill rakers and denticles towards the esophagus where they accumulate before being periodically swallowed. We infer three distinct morphotypes characterized by variations in geometry, mesh size, and surface structures, which indicate variations of the general mechanism. Discussion The description presented in this study contributes to the development of models for investigating the influence of morphological variation on fluid flow and particle retention in filter-feeding fish and on their ecology and biomimetic application.